Deposition of Bi2S3 thin films from heterocyclic bismuth(III) dithiocarbamato complexes. (1st November 2018) - Kun, Walter N.; Mlowe, Sixberth; Nyamen, Linda D.; Akerman, Matthew P.; O'Brien, Paul; Ndifon, Peter T.; Revaprasadu, Neerish
Graphical abstract: We report the structure of an orthorhombic tris -(piperidinyldithiocarbamato)bismuth(III) complex and its use as single source precursor for the deposition of orthorhombic bismuthinite (Bi2 S3 ) thin films in the leaf/plate like morphology. Abstract: Two heterocyclic dithiocarbamate complexes, tris -(piperidinedithiocarbamato)bismuth(III) (1 ) and tris -(tetrahydroquinolinedithiocarbamato)bismuth(III) (2 ) were synthesized and characterized by elemental analysis and thermogravimetric analysis. The structure of complex (1 ) was confirmed by single-crystal X-ray analysis. Both complexes were used as single source precursors for the deposition of bismuth sulfide thin films by aerosol assisted chemical vapour deposition (AACVD) at 350, 400, 450 °C and spin coating followed by thermal treatment at 350 °C, 400 °C and 450 °C. Both deposition methods, gave sulfur deficient polycrystalline films of bismuthinite. Scanning electron microscopy (SEM) images of the films showed morphology was dependent on the solvent mixture, temperature, precursor type and method of deposition. AACVD gave films with hexagonal nanoplatelets, leaf-like platelet, ribbon-like fibre, needle-like fibre morphologies. Films in the form of rods and interwoven nanowires were obtained from spin coating.